2015
DOI: 10.1002/2014jd022629
|View full text |Cite
|
Sign up to set email alerts
|

The first UK measurements of nitryl chloride using a chemical ionization mass spectrometer in central London in the summer of 2012, and an investigation of the role of Cl atom oxidation

Abstract: The first nitryl chloride (ClNO 2 ) measurements in the UK were made during the summer 2012 ClearfLo campaign with a chemical ionization mass spectrometer, utilizing an I À ionization scheme.Concentrations of ClNO 2 exceeded detectable limits (11 ppt) every night with a maximum concentration of 724 ppt. A diurnal profile of ClNO 2 peaking between 4 and 5 A.M., decreasing directly after sunrise, was observed. Concentrations of ClNO 2 above the detection limit are generally observed between 8 P.M. and 11 A.M. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 75 publications
(236 reference statements)
7
116
5
Order By: Relevance
“…Tham et al, 2016). However, the ratios are substantially higher than those measured in other megacities, e.g., Hong Kong (0.1-2.0; Wang et al, 2016), London (0.02-2.4;Bannan et al, 2015), and Los Angeles, California (0.2-10.0; Mielke et al, 2013). These results indicate ubiquitously high ClNO 2 /N 2 O 5 ratios in the NCP, consistent with another measurement in suburban Beijing , which might result from the high ClNO 2 production rate due to high aerosol loadings.…”
Section: Relationship Between N 2 O 5 and Clnomentioning
confidence: 57%
See 4 more Smart Citations
“…Tham et al, 2016). However, the ratios are substantially higher than those measured in other megacities, e.g., Hong Kong (0.1-2.0; Wang et al, 2016), London (0.02-2.4;Bannan et al, 2015), and Los Angeles, California (0.2-10.0; Mielke et al, 2013). These results indicate ubiquitously high ClNO 2 /N 2 O 5 ratios in the NCP, consistent with another measurement in suburban Beijing , which might result from the high ClNO 2 production rate due to high aerosol loadings.…”
Section: Relationship Between N 2 O 5 and Clnomentioning
confidence: 57%
“…Previous studies have found that N 2 O 5 and ClNO 2 were generally positively correlated in predominantly continental air masses, whereas they were negatively correlated in marine air masses with high chloride content (Bannan et al, 2015). Phillips et al (2012) also reported large variability in N 2 O 5 and ClNO 2 correlations and ClNO 2 /N 2 O 5 ratios in air masses from continental or marine origins due to the changes in particle Cl − .…”
Section: Relationship Between N 2 O 5 and Clnomentioning
confidence: 96%
See 3 more Smart Citations